Incomplete conquests the limits of Spanish empire in the seventeenth-century Philippines - Mawson, Stephanie Joy 1984- (Cornell University Press, 2023)
"This book tells a story of the limitations of empire, unearthing histories of resistance, flight, evasion, conflict, and warfare from across the breadth of the Philippine archipelago during the seventeenth century."-- Provided by publisher.